Photoluminescence from ultrathin Ge-rich multiple quantum wells observed up to room temperature: Experiments and modeling - Wendav, T.; Fischer, I. A.; Virgilio, Michele; Capellini, Giovanni; Oliveira, F.; Cerqueira, M. F.; Benedetti, Alessandro; Chiussi, Stefano; Zaumseil, P.; Schwartz, Bernhard; Busch, Kurt; Schulze, Jörg (Physical Review B, 2016)
Employing a low-temperature growth mode, we fabricated ultrathin Si1-xGex/Si multiple quantum well structures with a well thickness of less than 1.5 nm and a Ge concentration above 60% directly on a Si substrate. We identified an unusual temperature-dependent blueshift of the photoluminescence (PL) and exceptionally low thermal quenching. We find that this behavior is related to the relative intensities of the no-phonon (NP) peak and a phonon-assisted replica that are the main contributors to the total PL signal. To investigate these aspects in more detail, we developed a strategy to calculate the PL spectrum employing a self-consistent multivalley effective mass model, in combination with second-order perturbation theory. Through our investigation, we find that while the phonon-assisted feature decreases with temperature, the NP feature shows a strong increase in the recombination rate. Besides leading to the observed robustness against thermal quenching, this causes the observed blueshift of the total PL signal.
CRIS-Team Scopus Importer:2021-06-29